2010
DOI: 10.1124/jpet.110.165498
|View full text |Cite
|
Sign up to set email alerts
|

Identification of β-Escin as a Novel Inhibitor of Signal Transducer and Activator of Transcription 3/Janus-Activated Kinase 2 Signaling Pathway that Suppresses Proliferation and Induces Apoptosis in Human Hepatocellular Carcinoma Cells

Abstract: The activation of signal transducer and activator of transcription 3 (STAT3) has been linked with the proliferation, survival, invasion, and angiogenesis of a variety of human cancer cells, including hepatocellular carcinoma (HCC). Agents that can suppress STAT3 activation have potential for the prevention and treatment of HCC. In this study, we tested an agent, ␤-escin, for its ability to suppress STAT3 activation. We found that ␤-escin, a pentacyclic triterpenoid, inhibited both constitutive and interleukin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 129 publications
(94 citation statements)
references
References 38 publications
6
85
1
Order By: Relevance
“…This study is consistent with the earlier observations that support possible antitumorigenic effects of b-escin in in vitro and in vivo models (6)(7)(8)(9)(10). Previously, we showed that b-escin, at 250 and 500 ppm in the diet, inhibited colon carcinogen-induced preneoplastic foci in rat colon in a dose-dependent manner (6).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This study is consistent with the earlier observations that support possible antitumorigenic effects of b-escin in in vitro and in vivo models (6)(7)(8)(9)(10). Previously, we showed that b-escin, at 250 and 500 ppm in the diet, inhibited colon carcinogen-induced preneoplastic foci in rat colon in a dose-dependent manner (6).…”
Section: Discussionsupporting
confidence: 81%
“…Studies from our laboratory showed that b-escin inhibits the growth of colon cancer cells and inhibits chemically induced colon carcinogenesis in rats (6). In recent years, several studies have shown that b-escin possesses anticancer activity by inhibiting growth and inducing apoptosis in various human cancer cell lines derived from lung (7), pancreatic (8), and liver (9) cancers and in leukemia and multiple myeloma (10).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a clear link between hepatitis C virus (HCV), STAT3 activation and HCC development has been reported (Waris and Siddiqui 2005;Yoshida et al 2002). As described by many studies, STAT3 represents a good candidate as a target in HCC patients for therapeutic agents including natural compounds Rajendran et al 2011a, b;Tan et al 2010). …”
Section: Involvement Of Stat3 In Cancermentioning
confidence: 99%
“…Therefore, it is very important to identify new effective drugs. Among natural compounds from a variety of plants, diosgenin , b-escin (Tan et al 2010), butein ) and c-tocotrienol (Rajendran et al 2011a) were reported to inhibit proliferation and to induce apoptosis of HCC cells concomitantly in order to downregulate various STAT3-regulated gene products, including cyclin D1, Bcl-2, Bcl-xL, survivin, Mcl-1 and VEGF. These four natural molecules inhibited constitutive and inducible activation of STAT3 through the inhibition of c-Src, JAK1 and JAK2 activation.…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…We found that b-escin downregulated the expression of various STAT3 regulated gene products, such as cyclin D1, Bcl-2, Bcl-xL, survivin, Mcl-1, and VEGF. b-escin, in combination with paclitaxel or doxorubicin, potentiated the apoptotic effects of the chemotherapeutic compounds, thus its potent suppression of proliferation and chemosensitization of hepatocellular carcinoma [113,114]. In combination with 5-FU, b-escin showed a synergistic cytotoxic effect in human hepatocellular carcinoma SMMC-7721 by inhibiting induction of apoptosis, cell cycle arrest, activation of caspases-3, 8 and 9, and down-regulation Bcl-2 expression [115].…”
Section: Escinmentioning
confidence: 99%